Ratio Legis Kewenangan Diskresioner Kementerian Kesehatan Terkait Regulasi Komersialisasi Vaksin Gotong Royong Corona Virus Disease- 2019 (COVID-19) - Dewi Nawang Wulan; Devi Ayunda Rahma; Abdul Ghofur; Benny Djudjuren Tarigan (Faculty of Law Hang Tuah University, 2022)
Regulation of the Minister of Health the Republic of Indonesia No. 18 of 2021 on Changes to the Regulation of the Minister of Health the Republic of Indonesia No. 10 of 2021 on the Implementation of Vaccination in the Framework of Prevention of Coronavirus Disease Pandemic 2019 (COVID-19) as a reference for the implementation of vaccination programs led to a research analysis on the ratio legis of the regulation of commercialization of gotong royong vaccine for legal entities or business entities. Meanwhile, reviewed based on presidential Regulation No. 14 of 2021 on Changes to Presidential Regulation No. 99 of 2020 on Vaccine Procurement and Vaccination Implementation in the framework of Countering the Corona Virus Disease Pandemic 2019 (COVID-19) does not regulate the commercialization of gotong royong vaccine for legal entities or business entities so that the expansion of authority or discretion is seen from the Regulation of the Minister of Health of the Republic of Indonesia Number 18 of 2021, On the other hand, ministerial decisions that are beschikking / decree are reviewed based on the method of the legislative approach and the concept approach has exceeded the above regulations. The result of this study is that the ratio of legis to support the acceleration of pandemic response and the implementation of vaccination in the scope of force Majeure circumstances is required to assist legal entities, or business entities where it is regulated under the Regulation of the Minister of Health of the Republic of Indonesia interpreted in Presidential Regulation 99 of 2020 Article 17 paragraph (1) letter b included in other sources of legitimate vaccine procurement funding.